P.083 Trigeminal neuralgia caused by an intra-axial glioma in a child: first surgical case report and systematic review. (17th June 2016) - Bokhari, R; Baeesa, S; Sabbagh, A; Atkinson, J; Dudley, R; Farmer, J
Abstract : Background: Trigeminal neuralgia (TGN) is usually caused by arterial compression of the trigeminal nerve. There are very few cases caused by intra-axial brainstem masses. Little information is therefore available regarding the response to incomplete resection of offending lesions. We present one such case, and systematically review the published in the literature.Methods: Case report and systematic review of MEDLINE and EMBASEResults: Case report: A seven year-old girl is referred with typical TGN pain. MRI revealed a cervicomedullary tumor with no abnormalities of the pons or trigeminal nerve. Subtotal resection under neurophysiologic monitoring was achieved, leaving a small residual attached near the expected location of the trigeminal spinal nucleus and tract.Patient recovered well with resolution of her TGN pain. She is asymptomatic seven years post-operatively.Literature Review: We found no other published cases in children or secondary to gliomas. Among reviewed cases, only two underwent surgery. Both were adults with brainstem cavernomas and both reported substantial improvement despite incomplete resection.Conclusions: Our case as well as literature review both show that surgical resection is beneficial in such cases and, even if subtotal, can result in substantial pain relief. This suggests intra-axial compression of the trigeminal spinal nucleus and tract as the possible cause of TGN pain in such cases.